CHALLENGES AND OPPORTUNITIES FOR DEVELOPMENT OF ORGANIC PRODUCTION IN BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper examines the development of the organic production sector in Bulgaria in recent years, particularly emphasizing the main challenges and problems and the need for close monitoring, support and re–energisation of the sector. Its potential, trends and multidimensional implications for the environment, society and local communities represent an important research subject and are the focus of the INVEST Regional Living Lab in Bulgaria, established by the University of Agribusiness and Rural Development. The Living Lab applies the quadruple helix approach to work on open innovations that fits very well the research task of identifying challenges and opportunities for the development of organic production in Bulgaria. Combining primary data, case studies and facticology from the terrain that highlight the most pressing issues for regulation and funding, the research provides a two–level view of trends on organics at EU level and the local photography. The results suggest that improving the capacity of chain operators, access to organic markets and research on fast–growing ones can expand the potential of opportunities, integrating this research with other research tasks in the INVEST Living Laboratory in Bulgaria, especially those related to alternative food networks and relationships between urban and rural territories, climate change, agriculture and tourism. Good practices, green innovations and expertise within the ecosystem to implement efficient solutions remain essential for the vision and expansion of the sector.